A coupled-mode model for the transformation of wave systems over inhomogeneous sea/coastal environment - Belibassakis, KA; Gerosthathis, ThP; Athanassoulis, GA (2010)
The transformation of the directional wave spectrum over an inhomogeneous sea/coastal environment is considered. Inhomogeneities include intermediate-water depth, strongly varying 3D bottom topography and ambient currents. The consistent coupled-mode model, developed by Athanassoulis and Belibassakis (1999), extended to three dimensions by Belibassakis et al. (2001) and applied to the transformation of wave systems over 3D bottom topography (Gerostathis et al 2008) is exploited for the calculation of the transfer function, connecting the incident wave with the wave conditions at each point in the field. This model is fully dispersive and takes into account reflection, refraction, and diffraction phenomena. In the present work, the coupled mode system is enhanced to account also for the effects of steady currents (Belibassakis et al, 2008), as well as, the effect of wave energy dissipation due to bottom friction and wave breaking. Numerical results obtained by the present model are compared with other models (as, e.g., Li et al 1993, Yoon et al 2004) and experimental measurements (Vincent and Briggs 1989), demonstrating the usefulness and practical applicability of the present method. Copyright © 2010 by ASME.